2022
DOI: 10.1111/nbu.12559
|View full text |Cite
|
Sign up to set email alerts
|

Mindful eating: what we know so far

Abstract: Mindful eating is increasingly being used to try to promote healthy eating and weight management. However, the term refers to a diverse set of practices that could have quite different effects on behaviour. This narrative review provides a guide to the concept of mindful eating as well as a comprehensive overview of research in the area. This includes the ways in which mindful eating has been operationalised and measured as well as evidence for effects and potential mechanisms of action. The research reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 159 publications
(221 reference statements)
0
18
0
Order By: Relevance
“…Although research on mindful eating has been used in various ways, experimental studies are relatively limited, and it is not yet possible to conclude whether mindful eating strategies impact diet. However, some evidence suggests that certain mindful eating strategies may be promising, such as decentering and attention to the sensory properties of food [ 23 ]. A previous review showed that a mindful eating intervention reduced cravings and excess caloric intake and helped maintain continued weight loss [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although research on mindful eating has been used in various ways, experimental studies are relatively limited, and it is not yet possible to conclude whether mindful eating strategies impact diet. However, some evidence suggests that certain mindful eating strategies may be promising, such as decentering and attention to the sensory properties of food [ 23 ]. A previous review showed that a mindful eating intervention reduced cravings and excess caloric intake and helped maintain continued weight loss [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…(2) considering one's thoughts and emotions as separate from oneself, also called decentering; and (3), acceptance of one's experiences, also called non-reactivity (Tapper, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While some scholars consider mindfulness a skill that can be practiced (e.g., Bishop et al, 2004 ), others consider it a dispositional trait present in every person (Brown and Ryan, 2003 ). Mindful eating is viewed as a process that involves three aspects: (1) bringing attention to present moment experience, that is, the process of eating, taste, smells, thoughts, and feelings that arise during a meal, as well as internal cues of hunger and fullness; (2) considering one's thoughts and emotions as separate from oneself, also called decentering; and (3), acceptance of one's experiences, also called non-reactivity (Tapper, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations